2011
DOI: 10.1016/j.ajo.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Vitrectomy for Floaters

Abstract: The risk profile of vitrectomy for floaters is comparable with that of vitrectomy for other elective indications. Retinal breaks are a common finding during surgery and treatment of these breaks is crucial for the prevention of postoperative retinal detachment. Patients considering surgery for floaters should be informed specifically about the risks involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 13 publications
(27 reference statements)
0
60
3
3
Order By: Relevance
“…Intra-operative iatrogenic retinal breaks were found in 16.4% of patients and also retinal detachment occurred in 10.9% of cases (de Nie et al, 2013;Tan et al, 2011;Schulz-Key et al, 2011).…”
Section: Treatmentmentioning
confidence: 94%
“…Intra-operative iatrogenic retinal breaks were found in 16.4% of patients and also retinal detachment occurred in 10.9% of cases (de Nie et al, 2013;Tan et al, 2011;Schulz-Key et al, 2011).…”
Section: Treatmentmentioning
confidence: 94%
“…In the study by de Nie et al, 21 of 50 eyes with clear lens before surgery, 19 eyes (38%) underwent cataract surgery during a period of 26.4 months. FOV with sparing of anterior vitreous is theoretically more lens friendly and the reported rate of cataract formation is lower at 23.5% (over 15 months) and 22.5% (over 18 months) in the two large studies by Sebag et al 39 and Mason et al 23 There is a great variation in literature in the incidence of RD post-PPV for SVO with figures ranging from 0, 2,32 2, 31 2.5, 6 6.7, 30 and 6.8%, 5 to as high as 10.9%. 21 Other complications following PPV for SVO include CMO (0.6-5.5%), 5,21,23 epiretinal membrane formation (1.3-3.6%), 6,21,39 transient vitreous haemorrhage (1.2%), 23 glaucoma (0.9%), 21 macular hole (0.9%), 21 and postoperative scotoma (0.9%).…”
Section: Summary Of Various Studies On Ppv For Svomentioning
confidence: 94%
“…This rate is less than that reported in literature (38-60%). 5,6,21 Also in this study the authors have not given the mean age of the phakic group, although the mean age of all patients in their study was 63 years (range 41-87 years). A quality of life survey in this group using a modified nine-QOL questionnaire showed that 96% of patients were satisfied with the surgery, with 94% calling it a complete success.…”
Section: Floaters-only-vitrectomy Recently Sebag Et Almentioning
confidence: 99%
See 2 more Smart Citations